2019
DOI: 10.1002/job.2364
|View full text |Cite
|
Sign up to set email alerts
|

Different motivations for knowledge sharing and hiding: The role of motivating work design

Abstract: Summary Little research to date has focused on understanding employee motivation to share and hide knowledge. Using self‐determination theory, we tested the premise that knowledge sharing and hiding might be differentially motivated and that work design characteristics might influence the motivation to share knowledge with colleagues. In a panel survey of Australian knowledge workers and in a Chinese knowledge‐intensive organization, we asked knowledge workers, using time‐lagged designs, about perceptions of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
287
3
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(307 citation statements)
references
References 80 publications
11
287
3
6
Order By: Relevance
“…Expert users must perceive interactivity with service firms housed in the virtual community to participate in co-innovation activities. These results agree with those obtained by [63], according to which virtual community users with a higher level of expertise discriminate in the audience they address when they participate in the co-creation process. Their altruism moves them to perform moderate co-creation behavior: Recommendation of the service.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Expert users must perceive interactivity with service firms housed in the virtual community to participate in co-innovation activities. These results agree with those obtained by [63], according to which virtual community users with a higher level of expertise discriminate in the audience they address when they participate in the co-creation process. Their altruism moves them to perform moderate co-creation behavior: Recommendation of the service.…”
Section: Discussionsupporting
confidence: 90%
“…Such understanding can then be transformed into a favorable opinion of the products/services commercialized and better organizational reputation [60]. More frequent, faster, richer communication between user and company in the virtual community are passionately and emotionally linked to both participants [63], enhance the feeling of being engaged with the organization [61], and drive users to participate in the value co-creation process, supporting the firm by recommending its brands, products, and/or services.…”
Section: Hypothesis 1c (H1c) the User's Altruism Positively Influencmentioning
confidence: 99%
“…The implementation of knowledge management can be thought of in two different ways [70,71]. The first is that there is a possibility that knowledge management to increase the autonomy of the medical staff by enhancing knowledge access.…”
Section: Knowledge Management and Organisational Learningmentioning
confidence: 99%
“…Consequently, coaching behavior could serve as an incentive to motivate employees to perform proactive and voluntary behavior (e.g., knowledge sharing). Researchers have noted that motivation is a crucial antecedent to knowledge sharing (Gagné, 2009;Gagné et al, 2019). For example, Gagné et al (2019) demonstrated that autonomous motivation (i.e., "reason to" motivation) is positively related to knowledge sharing.…”
Section: Coaching Behavior and Knowledge Sharingmentioning
confidence: 99%
“…Researchers have noted that motivation is a crucial antecedent to knowledge sharing (Gagné, 2009;Gagné et al, 2019). For example, Gagné et al (2019) demonstrated that autonomous motivation (i.e., "reason to" motivation) is positively related to knowledge sharing. Accordingly, we propose the following hypothesis:…”
Section: Coaching Behavior and Knowledge Sharingmentioning
confidence: 99%